Risk of HBV infection among male and female first-time blood donors born before and after the July 1986 HBV vaccination program in Taiwan - Hsuan-Hui Wang; Shu-Lung Sun; Rong-Chiou Jau; Disline Manli Tantoh; Shu-Yi Hsu; Oswald Ndi Nfor; Pei-Hsin Chen; Wen-Hsiu Liu; Jiunn-Liang Ko; Yung-Po Liaw (BMC, 2021)
Abstract Background In July 1984, Taiwan officially began a nationwide hepatitis B virus (HBV) vaccination program where only infants born to HBsAg-positive mothers were vaccinated free of charge until June 1986. However, from July 1986, all infants were vaccinated against HBV. The impact of the July 1986 HBV vaccination program on first-time blood donors has not been exhaustively studied. We, therefore, determined the risk of HBV among male and female first-time blood donors born before and after the July 1986 HBV vaccination program in Taiwan. Methods Initially, we recruited 857,310 first-time blood donors whose data were collected between 2013 and 2018 from 5 blood donation centers in Taiwan. However, we excluded donors with incomplete and outlying data (n = 12,213) and those born between July 1984 and June 1986 (n = 21,054). The final study participants comprised 9118 HBV positive and 814,925 HBV negative individuals. We divided the participants into two birth cohorts (born before and after July 1986) and assumed that those born before July 1986 were not vaccinated at birth while those born after July 1986 were vaccinated. Results The prevalence of HBV among those born before and after July 1986 was 4.53 and 0.25%, respectively. Individuals born after July 1986 had a lower risk of HBV than those born before July 1986. The adjusted odds ratio (OR), 95% confidence interval (CI) was 0.16, 0.13-0.19. Men had a higher risk of HBV than women (OR = 1.40, 95% CI = 1.34-1.47). The interaction between sex and birth date was significant (p-value = 0.0067). Stratification of participants by birth date revealed a higher risk of HBV in men compared to women in both birth cohorts. The OR, 95% CI was 1.47, 1.40-1.55 for those born before July 1986 but declined to 1.15, 1.02-1.29 for those born after July 1986. Conclusions The risk of HBV was lower among those born after than those born before the July 1986 vaccination program. In both cohorts, the risk was high in men relative to women. The seemingly protective effect among those born after July 1986 was higher in women than men.